'The greatest Slovak' in the historical memory of modern Slovakia - O.S. Krylova; G.V. Rokina (Ученые записки Казанского университета: Серия Гуманитарные науки)
The development and preservation of historical memory in the Slovak Republic were discussed using the Slovak pantheon of national heroes as an example. The study aims to show commemorative practices used in the historical development of the country. The mechanisms and tools for defining the collective historical memory of Slovaks in the modern times were considered. Some examples of the political use of memories of the past were analyzed. The title of the paper traces back to the public survey about “the greatest Slovak” arranged by the Slovak radio station and television in May 2018–October 2019. A number of examples illustrating the process of formation of historical myths and stereotypes in the collective historical memory of Slovaks over several centuries were provided. In modern Slovakia, the public is generally rejecting the old stereotypes and new myths are emerging against the background of heated discussions between politicians and historians. A simultaneous destruction of the old “places of memory” and the formation of the new ones is taking place. Furthermore, the traditional pantheon of Slovak national heroes is being updated. These processes have a considerable influence on the development of the country. In this work, special attention was paid to such historical figures of Slovakia as L. Štúr, the Founding Father of the Slovak nation, and M.R. Štefánik, the outstanding politician. The results of the television survey were analyzed in detail: the public had to choose 100 most outstanding personalities of the Slovak history, politics, and culture, as well as to determine “the greatest Slovak” among them. The latter title was finally awarded to M.R. Štefánik. It was concluded that the collective historical memory in Slovakia is at its early stage of development and that Slovaks have not fully overcome the myths and stereotypes of the past.